Investigating the ESP Present, Target, and Learning Needs of Architecture Students: A Case Study of Master 1 Students at the University of Laghouat - BEN HARZALLAH ,Iman; MUSTAPHA ,Yasmine (Faculty of Letters and Foreign Languages Department of English, 2025)
English for Specific Purposes (ESP) in Algerian higher education often lacks contextualization and systematic needs analysis, as a result, many courses are irrelevant to students' real academic and professional needs. In response to this situation, the present study aimed at investigating the perceived and real English language needs of the Master 1 architecture students at the University of Laghouat, their problems in English language acquisition, and whether the existing ESP course meets their needs. A mixed-method design was used to collect data, combining quantitative and qualitative tools. To explore students’ perceived and real needs, a needs analysis questionnaire, adapted from Target Situation Analysis (TSA), Present Situation Analysis (PSA), and Deficiency Analysis (DA), was administered to 23 students. Furthermore, a language proficiency test was developed to measure their real performance in several language skills, classroom observations were carried out to investigate teaching practices and student interaction, and a semi-structured interview with the English teacher provided additional understanding of pedagogical and institutional challenges. The results indicated that even though students were highly motivated to use English in professional and academic contexts, especially in speaking and writing, these skills were not emphasized and were underdeveloped in the classroom. Their strongest skill seemed to be reading , however this might be because of the exposure to simplified texts, while their major challenge was in technical vocabulary, which hindered their ability to access authentic resources. The teacher interview confirmed these results, showing that there is no systematic needs analysis conducted, the over-focus on reading, and the lack of collaboration with language specialists. The study determines that there is a clear gap between what the students actually require and what the ESP course currently provides. It demonstrates the necessity to reformulate a more practical, relevant and needs-based curriculum that helps architecture students in their academic as well as professional lives.